SOLAR TRACKING SYSTEM DENGAN ARDUINO NANO DAN SENSOR LDR: PANEL SURYA BERGERAK MENGIKUTI ARAH CAHAYA - Fazilatunnisa, Azwa; Mochamad Yogi Febriansyah; Firdaus; Ahmad Fauzul Mubin; Daffa Wahid Sya'bani; Dony Hutabarat (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2025)
This study discusses the design of a single-axis light tracking system based on an Arduino Nano microcontroller. The system is designed to automatically direct solar panels to follow the direction of incoming light using two LDR sensors and one servo motor. The LDRs detect light intensity on the left and right sides, while the Arduino controls the comparison logic to move the servo according to the direction of the dominant light. Functional testing was conducted indoors using artificial light. Observation results indicate that the system responds well to light direction. The servo's movement aligns with changes in light intensity, though there is a response delay of approximately 1–2 seconds. The system also demonstrates stability when light intensity is balanced, indicating that the control logic operates effectively. The system's limitations lie in its horizontal movement range and the fact that it has not been tested outdoors. Nevertheless, this prototype can serve as a foundation for developing a two-axis tracking system or integrating it with the Internet of Things (IoT) for further applications.